Follitropin Alpha versus Follitropin Beta in IVF/ICSI Cycle: A Retrospective Cohort Study - Cao JX; Song JY (Dove Medical Press, 2024)
Jing-Xian Cao,1 Jing-Yan Song2,3 1Gynecology, Binzhou Hospital of Traditional Chinese Medicine, Binzhou, People's Republic of China; 2The First Clinical College, Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China; 3Reproductive Center of Integrated Medicine, The Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of ChinaCorrespondence: Jing-Yan Song, The First Clinical College, Shandong University of Traditional Chinese Medicine, Reproductive Center of Integrated Medicine, The Affiliated Hospital of Shandong University of Traditional Chinese Medicine, No. 42, Wen Hua Xi Road, Lixia District, Jinan, 250011, People's Republic of China, Tel +86-0531-68617921, Email hanlingjuzei91@126.comPurpose: The purpose of this study was to compare the efficacy of Follitropin alpha (Gonal-F) and Follitropin beta (Puregon) on cumulative live birth rate (CLBR), defined as the percentage of the number of patients who delivered for the first time in a single ovarian stimulation cycle and the number of patients in all oocyte retrieval cycles.Methods: A retrospective cohort study including 2864 infertile patients who underwent ovarian stimulation with Puregon (group A, n=1313) and Gonal-F (group B, n=1551) was conducted between July 2015 and June 2021 at a university-affiliated reproductive medicine center. Reduce potential confounding factors between groups, propensity scores and multivariable logistic regression analyses were estimated to obtain unbiased estimates of outcomes. The primary outcome was the difference in CLBR between the two groups.Results: Each group identified 1160 individuals after propensity score matching (PSM). Baseline characteristics were similar between groups after PSM. The total gonadotrophin (Gn) dose (2400 vs 2325), p=0.038) and cost of Gn usage (5327.9¥ vs 7547.2¥, p< 0.001) between the Puregon and Gonal-F groups were statistically significant. Nevertheless, the pregnancy outcomes between the two groups were comparable after fresh embryo transfer and subsequent frozen-thawed embryo transfer. Additionally, there was also no difference observed in the primary outcome of CLBR (52.8% vs 55.7%, p=0.169). Multivariable regression analysis revealed that the type of Gn was not associated with CLBR (p = 0.912).Conclusion: Gonal-F may be a reasonable option for infertile patients who are hesitant to receive more Gn dosage injections. Furthermore, Puregon can eliminate unneeded anxiety and expenses while also administering more flexibility. Taken together, these findings could well be utilized in everyday clinical practice to better inform patients when deciding on an ovarian stimulation strategy.Keywords: cumulative live birth rate, follitropin alpha, follitropin beta, in vitro fertilization, propensity score matching